Are acceptance, support, and the factors that affect them, different? Examining perceptions of U.S. fuel economy standards. (August 2015) - Dreyer, Stacia J.; Teisl, Mario F.; McCoy, Shannon K.
Highlights: Acceptance and support are differentiated on two dimensions. Acceptance of fuel economy standards is higher than support for the standards. The added behavioral cost of support may explain the above difference. Determinants of policy acceptance and policy support differ. Abstract: Understanding the acceptance of and support for transportation policies focused on the environment, such fuel economy standards, is important because of the positive impact policies can have on the environment and overall sustainability goals. This study investigates the acceptance of and support for fuel economy standards through an online survey of Maine residents. Specifically, we assess the Corporate Average Fuel Economy (CAFE) standards, which aim to increase fuel economy of vehicles, while decreasing greenhouses gas emissions and foreign fuel dependence in the United States. We assess how perceptions of the policy and economic views of the market affect acceptance and support. We differentiate acceptance and support on two dimensions, a temporal and attitudinal–behavioral dimension. In doing so, we improve upon traditional measures of these variables and provide evidence that acceptance and support are distinct constructs. We find that perceived fairness, perceived effectiveness, and a subscription to a free-market ideology play a role in acceptance and support. The implications of the findings are discussed in relation to survey methods, policy communications, and an interdisciplinary understanding of environmental policy.